Pengaruh Prosentase Etanol terhadap Torsi dan Emisi Motor Indirect Injection dengan Memodifikasi Engine Control Module - Rahmad, Hadi; Sasongko, Mega Nur; Wijayanti, Widya (Rekayasa Mesin, 2016)
This research present the torque and exhaust emission level from four stroke indirect injection fuel system engine. An engine fueled by ethanol gasoline blend. The original Engine Controle Module injected lean mixture into Combustion Chamber. Lean Mixture decreased Torque drastically. Therefore, the Engine Controle Module was modified to produce stoichiometric mixture. Injector was controlled by digital pulse of Fuel Controller. Ethanol was added into gasoline 0% - 100% at 1500 rpm-5000 rpm. The result demonstrate that increasing ethanol concentration into gasoline fuel system, decreasing Torque, and CO, HC, CO2 emission. By increasing ethanol concentration also increase CO2 emission to 34.6%.